Splat the cat and the late library book ebook - Scotton, Rob (Splat the Cat., 2016)
New York Times bestselling author Rob Scotton brings readers yet another laugh-out-loud Splat the Cat adventure! When Splat discovers that he has an overdue library book, he fears that he will be locked up in jail! He does whatever he can to avoid the library. But when he has to go there with his family, he is in for a happy surprise. Fans of Splat the Cat will love this hilarious, all-new 8x8 picture book.